A história de Iago: o menino guerreiro no mundo da comunicação alternativa - Forchetti, Daniella (2000)
This research goal is to study the construction of the multi handicapped autonomy throujh a speech therapy. In this process an alternative communication system, basen on Jean Van Dijk studies, was used. He demonstrated that multihandicapped children have difficulties in distinguishing themselves, the others being extensions of their own bodies. Therefore, separating oneself from the others is essential for their representative and symbolic attitude indispensable to their language development. The child discovers that his body is a vehicle with which he will explore the world throujh movement and thoujh out an adult/therapist interaction. More than widely discuss the theme multihandicapped child s language this work s perspective is to valorize the therapeutic process the respect to differences; to realize the necessary adaptations so that the patient can communicate; a on the must autonomous way possible. Only then he will be able to navigate to his independency